The relation of diet to certain chronic diseases - Tolin, Anna R. (My University, 1907)
Introduction: Disease means want of ease and wherever found it is a sure sign that something is wrong. Discomfort is one of the earliest signs of its approach, pain is a later one. They both are warnings that sooner or later sickness will overtake us if proper steps are not taken to prevent it. As disease is the result of the violation of the laws of health, the first advance toward recovery is to reestablish those laws. Life depends upon diet and the restoration of health depends upon the same principles as its preservation; as the material for repair and support must come from diet we should have a practical knowledge of dietaries and a proper appreciation of their curative value.
Citation: Tolin, Anna R. The relation of diet to certain chronic diseases. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Diet; Chronic Diseases; Health; Types of Diseases; Causes of Disease; Disease Treatment; Theses